Legal Service Unit and Teacher Protection as A Mediation Forum for Penal Violence in the World of Education - Aman Serah, Yenny (Advances in Social Sciences Research Journal, 2021)
This study offers a development of a model of fair teacher protection, with a focus on research conducted in West Kalimantan, particularly in Pontianak City and Ketapang District. The offer of a just teacher protection model is based on the empirical facts that there is still violence in the world of education and/or the criminalization of teachers that is still happening. Although various laws and regulations have been regulated to provide legal protection for teachers, the mechanism for implementing legal protection for teachers has not yet been formulated, so the reality is that when problems occur in the world of education and/or criminalization of teachers, they are resolved in various ways, either through government agencies, teacher organizations, schools or police officers, and there are even mutual opinions on social media. Through the socio-juridical research method through interviews and discussions, it was found that the effort to provide legal protection for teachers is important to be regulated through regional policies related to the formation of the Legal Service Unit and Teacher Protection or Unit Pelayanan Hukum dan Perlindungan Guru (UPHPG) which can become a coordinating institution and a forum for solving legal problems for teachers. The focus of this article describes how the UPHPG is intended to be a mediation platform for penal mediation in resolving violence in education and/or criminalizing teachers.